Using AR to Enhance the Learning of Chirality - Martin Bullock; Johannes Huwer (Education Sciences)
This study investigates the use of Augmented Reality (AR) to teach the concept of chirality—a fundamental topic in organic chemistry. Building on Cognitive Load Theory (CLT) and previous research on AR’s educational benefits, we designed an AR learning environment to facilitate students’ understanding of chirality by allowing them to interact with and superimpose virtual and physical models of chiral molecules. An initial pilot study involving 11th-grade students revealed positive student attitudes towards AR, with participants reporting enhanced comprehension of chirality and a preference for AR-based learning over traditional methods. The follow-up study refined the AR lesson based on pilot feedback, extending its scope to introduce, rather than review, the concept of chirality. Results indicated significant learning gains, low extraneous cognitive load, and high acceptance of AR technology among students. These findings underscore the potential of AR to support complex spatial learning in chemistry, though further research, such as value-added studies, is recommended to explore the generalizability and long-term impacts of AR on different student populations.